Pengurangan Aktivitas Non-Value AddedDalam Alur Proses Pelayanan Kesehatan Dengan Pendekatan Lean Six Sigma - Rafika Hayati; Gesit Thabrani (Universitas Negeri Padang, 2019)
Purpose- This study aims to reduce Non-Value Activities in the Health Service Process flow using Lean Six Sigma Approach in the Outpatient department of LubukBuaya Health Center.Methodology - The research reported in this paper is based on a case study carried out using the lean six sigma DMAIC (Define-Measure-Analyze-Control) approach and its application in to reducing non-value activities in the health service process flowin the outpatient department of LubukBuaya health center in Padang. The analytical tools used in this study include value stream mapping, process capability, and fishbone diagram.Finding - From the results of the analysis and research that has been done it turns out thatThe lead time needed in the flow of the outpatient service process is 82.74 minuteswith percentage of process cycle efficiency is 15,03%, it means that the service process to the outpatients is not yet efficient. It is caused by several factors such as there is no online registration application, the number of visits increases at certain hours, and use of the patient's electronic database that is not optimal. Keywords: Reduce, Non-Value Activities, Lean six sigma, DMAIC, Health service, Outpatient.